Identification of Swimming Pool Sanitation in Banyuwangi: Study in Swimming Pool X at Glagah - Yuli Astuti; Septa Indra Puspikawati; Inriza Yuliandari (Universitas STRADA Indonesia, 2020)
The purpose of this research is to know the description of sanitation of swimming pool X Glagah in Banyuwangi. This research used observation and interview technique. The research was on June, 2017, took place in swimming pool X Glagah in Banyuwangi. The observation and Interview performed using an research instrument. The research instrumen based on Minister of health of Republic of Indonesia Regulation No. 416 of 1990 about requirement and monitoring water quality, and Minister of Tourism of Republic of Indonesia No. 16 of 2015 about swimming pool business standard. The observation instrument contains five variables. There are water quality of swimming pool, sanitasion facility, health of building and environment, health of room, and evaluation for employees. There are three variables on interview instrument. There are product, services, and management